Thermochemical analysis of the behaviour of Cu in Ti nano-strand formation from low-temperature reaction of Al-Fe-Cu powder with CaF2-SiO2-Al2O3-MgO-MnO-TiO2 flux - Theresa Coetsee; Frederik Johannes De Bruin (Chemical Thermodynamics and Thermal Analysis)
The interaction between oxy-fluoride slag and metal in the submerged arc welding process (SAW) includes gas phase reactions. These reactions occur at elevated temperatures in the confined arc cavity, typically between 2000 °C and 2500 °C, making studying the specific chemical interactions challenging. To address this, an experimental method was applied at a lower temperature of 1350 °C to simulate and study the behaviour of the gas species generated from the oxy-fluoride flux, especially when combined with metal powders. In the current study, Al-Fe-Cu metal powders were reacted with CaF2-SiO2-Al2O3-MgO-MnO-TiO2 flux to identify the behaviour of copper in the reaction system. Post-reaction three-dimensional slag was analysed using energy dispersive X-ray spectroscopy (EDX) to locate and analyse nano-strands, which confirm gas phase reactions from the oxy-fluoride slag. Thermochemistry calculations explain the observed nano-strand formation from gas-slag-metal reactions. The analyses identified Ti nano-strands with Cu-Fe-Mn-Si fluoride end-caps. Thermochemical analysis indicates that the end-caps formed from oxy-fluoride vaporisation and re-condensation. Ti in the nano-strands originated from TiO2 in the slag. The following gas-based reaction explains the displacement of Ti by Al from Ti-fluoride gas: yAl + xTiFy ↔ xTi + yAlFx. The low-temperature experimental technique can be used to simulate oxy-fluoride slag behaviour in SAW fluxes in terms of gas formation and metal powder assimilation reactions as observed in the SAW process.